Hyperpolarized 129Xe MRI using isobutene as a new quenching gas. (16th August 2016) - Hodono, Shota; Imai, Hirohiko; Yamauchi, Yukiko; Kawamura, Ayano; Matsumoto, Hironobu; Okumura, Shintaro; Fujiwara, Hideaki; Kimura, Atsuomi
Abstract: The use of a quenching gas, isobutene, with a low vapor pressure was investigated to enhance the utility of hyperpolarized 129 Xe (HP Xe) MRI. Xenon mixed with isobutene was hyperpolarized using a home‐built apparatus for continuously producing HP Xe. The isobutene was then readily liquefied and separated almost totally by continuous condensation at about 173 K, because the vapor pressure of isobutene (0.247 kPa) is much lower than that of Xe (157 kPa). Finally, the neat Xe gas was continuously delivered to mice by spontaneous inhalation. The HP Xe MRI was enhanced twofold in polarization level and threefold in signal intensity when isobutene was adopted as the quenching gas instead of N2 . The usefulness of the HP Xe MRI was verified by application to pulmonary functional imaging of spontaneously breathing mice, where the parameters of fractional ventilation ( r a ) and gas exchange ( f D ) were evaluated, aiming at future extension to preclinical studies. This is the first application of isobutene as a quenching gas for HP Xe MRI. Abstract : The possibility of a quenching gas, isobutene, has been investigated to enhance the sensitivity and utility of hyperpolarized 129 Xe MRI. While the quenching ability of isobutene was comparable to that of N2, conventionally used as a quenching gas, the sensitivity in the case of isobutene was 2.8 times higher than for N2 because isobutene could be removed before delivering to mice. The usefulness of isobutene was verified by applying it to pulmonary functional imaging of spontaneously breathing mice.